The Cerebellum Links to Positive Symptoms of Psychosis: A Systematic Review and Meta-analysis. Issue 1 (23rd August 2021) - Pinheiro, Ana P; Johnson, Joseph F; Amorim, Maria; Roberto, Magda; Schwartze, Michael; Kotz, Sonja A; Shenton, Martha E
Abstract: Background: Positive symptoms of psychosis may be the result of faulty coordination and automatization of motor and higher order cognitive functions, partly due to cerebellar dysfunction. Specifically, auditory verbal hallucinations (AVH) have been related to altered processing of sensory feedback to one's own action. Such alterations highlight the role of dysfunctional cerebellar circuitry in psychosis. However, how exactly the cerebellum contributes to AVH remains unclear. Methods: A systematic search of electronic databases identified a broad range of cerebellar neuroimaging studies in psychotic patients, reporting volume, structural connectivity, or resting-state functional connectivity data. A total of 22 studies were selected for review: 11 focused on the specific effects of AVH and 11 probed the effects of aggregated positive symptom scores. Meta-analysis was used to probe the consistency of cerebellar differences and their relationship with sociodemographic and clinical measures. An exploratory activation likelihood estimation (ALE) analysis tested the regional specificity of cerebellar differences in patients with such symptoms. Results: Cerebellar differences were more consistently associated with AVH than with aggregated positive symptom measures, particularly when considering resting-state functional connectivity data. These differences were not moderated by age, sex, medication, or symptom severity. The ALE meta-analysis revealed a spatial convergence of these differences in lobules V–VI and crus I. Conclusions: Cerebellar dysconnectivity might indicate a specific liability for AVH, particularly in sensorimotor (lobules V–VI) and cognitive (crus I) cerebellar zones. These abnormalities may contribute to altered sensory feedback processing and, consequently, affect higher level cognitive functions (eg, cognitive control) in AVH.